2018
DOI: 10.1177/1082013218815285
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ozone treatment on the microstructure, chemical composition and sensory quality of apple fruits

Abstract: The aim of this study was to assess the effect of O 3 treatment on the quality of different cultivars of apples (Malus domestica Borkh.). Apples were stored for six months at different concentrations of ozone. During the research, minor differences between ozone-treated and control fruits were found in terms of cell integrity and epicuticular wax structure. Ozone application for apple treatment could accelerate the natural ageing of the waxes found on the surface of apples, thereby reducing the thickness of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…However, the changes of apple firmness were similar for Fuji apples under CA storage alone or supplemented with ozone gas ( Sheng et al, 2018 ). Accordingly, the application of gaseous ozone at 0.8 mg/L during 6 months of cold storage retarded the loss of flesh firmness in Ledzenu and Auksis apples ( Juhnevica-Radenkova et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the changes of apple firmness were similar for Fuji apples under CA storage alone or supplemented with ozone gas ( Sheng et al, 2018 ). Accordingly, the application of gaseous ozone at 0.8 mg/L during 6 months of cold storage retarded the loss of flesh firmness in Ledzenu and Auksis apples ( Juhnevica-Radenkova et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ozone gas application during storage is beneficial to maintain fruit quality. For example, 1–3 mg/L gaseous ozone exposure was reported to maintain the firmness of apples ( Antos et al, 2018 ) and reduced apple weight loss ( Juhnevica-Radenkova et al, 2019 ). We previously showed that 30 weeks of continuous application of gaseous ozone at 87 μg/L in CA storage reduced Listeria by ∼5.0 log 10 CFU/apple on Fuji apples without negatively impacting apple fruit quality ( Sheng et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The treatment also delayed apple fruit ripening through the reduction of firmness loss and titratable acidity while had no negative impact on fruit visual quality (Sheng et al., 2018). Six months of storage at 2°C and 85% RH with 0.8 ppm ozone significantly reduced spoilage of apples of various varieties compared with those stored without ozone gas (Juhnevica‐Radenkova et al., 2019). A 107‐day continuous exposure to 0.4 ppm ozone gas at 0°C reduced the ethylene production of apples and pears with no symptom of ozone burn or other quality deterioration (Skog & Chu, 2001).…”
Section: Antimicrobial Gasmentioning
confidence: 99%
“…The history of developing methods for storing fruit and vegetable products shows that atmospheric air and its components are used in most cases. Storage in artificially created gases (for example, ozone) has not found wide application in practice due to their high cost or low efficiency (for fruits) [9], [10], [11]. Based on the gas composition of atmospheric air and depending on the type of environment created on its basis, we conducted research on the storage of fruits and vegetables: -in a controlled atmosphere (CA); -in bioactive bactericidal packaging; -with a surface coating of fruits with biologically active preparations.…”
Section: Introductionmentioning
confidence: 99%